Нові для науки асоціації та субасоціації мохової рослинності Лісостепу України - Гапон, С.В. (Український ботанічний журнал, 2010)
Дана характеристика ассоциаций Orthodicrano montani-Hypnetum reptilis ass. nova, Ptilidio pulcherrimi-Hypnetum reptilis ass. nova, Plagiomnietum ass. nova и субассоциаций ассоциации Pleurozietum schreberi Wisn. 1930: dicranіetosum polyseti subass. nova, clavullinietosum rugosi subass. nova моховой растительности, обнаруженных на территории Лесостепи Украины. Characteristics are provided for new moss associations, Orthodicrano montani- Hypnetum reptilis ass. nova, Ptilidio pulcherrimi-Hypnetum reptilis ass. nova, Plagiomnietum undulati ass. nova, and subassociations: Pleurozietum schreberi Wisn. 1930: dicranetetosum polyseti subass. nova and clavulinietosum rugosi subass. nova. These syntaxa were found in the territory of the Ukrainian Forest-Steppe.